Conditioning strategies for improving handball throwing velocity: A systematic review and meta-analyses - Petruzela, J.; Papla, M.; Stastny, P. (Journal of Human Kinetics, 2023)
Ball throwing velocity is essential for scoring goals in handball; the crucial question is how to develop throwing velocity in highly trained handball players. Therefore, this systematic review aims to summarize effective conditioning strategies to improve throwing velocity in elite male players and to perform a meta-analysis on which training system can provide the highest increase in throwing velocity. The literature was analyzed using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) in PubMed, Scopus, and Web of Science. Thirteen studies (sample n = 174) were included: five resistance training studies, one core training study, one study on repeated shuffle sprint training with small-sided games, and one on eccentric overload training. Effect size comparison showed that resistance training is the most effective strategy for improving throwing velocity in elite handball players (d > 0.7). Core training showed a small effect (d = 0.35). Small-sided game (SSG) training showed different results, from a significant positive effect (d = 1.95) to a negative effect (d = -2.03), and eccentric overload training showed a negative effect (d = -0.15). Resistance training is the most effective strategy for improving throwing velocity in elite handball players, while core training and SSGs can improve throwing velocity in youth athletes. Due to the small number of studies focusing on elite handball players, there is a need for more studies on advanced resistance training methods, e.g., contrast, complex, ballistic training, because much greater demands are placed on handball performance assumptions.